Rising Wage Inequality in Germany: Increasing Heterogeneity and Changing Selection into Full-Time Work - Martin Biewen; Bernd Fitzenberger; Jakob de Lazzer (Institute of Labor Economics (IZA), 2017)
This study revisits the increase in wage inequality in Germany. Accounting for changes in various sets of observables, composition changes explain a large part of the increase in wage inequality among full-time workers. The composition effects are larger for females than for males, and increasingly heterogenous labor market histories play an important role. Furthermore, we find strong effects of education for males and strong effects of age and experience for females. Changes in industry and occupation explain fairly little. Extending the analysis to total employment confirms the basic findings, while revealing substantial negative selection into part-time work.
Keywords: J31; J20; J60; 330; composition effects; reweighting; wage inequality; Germany